1998
DOI: 10.1071/aj97008
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Forward Stratigraphic Modelling of Early Cretaceous Sedimentation on the Leveque and Yampi Shelves, Browse Basin

Abstract: Early Cretaceous clastic sedimentation on the Leveque and Yampi Shelf areas of the Browse Basin has been brought sharply into focus recently as a result of exploration success at Gwydion and Cornea. The changing nature of clastic sedimentation patterns in the shallow-to-deep marine environments during C. delicata to upper S. areolata times is of increasing exploration interest. This study was designed to address the following questions: Could the conceptual geological model discussed by Spry and Ward (1997) ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Sedsim is a 3D numerical hydraulic process‐response SFM package that simulates transport, deposition and erosion by solving approximations to the Navier‐Stokes fluid‐flow equations. Sedsim has seen extensive use in research and industry, from hydrocarbon exploration to predicting the effects of climate change (Tetzlaff and Harbaugh, ; Griffiths and Paraschivoiu, ; Griffiths and Dyt, ; Griffiths et al ., ; Wijns et al ., ; Salles et al ., ; Huang et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…Sedsim is a 3D numerical hydraulic process‐response SFM package that simulates transport, deposition and erosion by solving approximations to the Navier‐Stokes fluid‐flow equations. Sedsim has seen extensive use in research and industry, from hydrocarbon exploration to predicting the effects of climate change (Tetzlaff and Harbaugh, ; Griffiths and Paraschivoiu, ; Griffiths and Dyt, ; Griffiths et al ., ; Wijns et al ., ; Salles et al ., ; Huang et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…A series of Sedsim modules simulating sediment transport, subsidence, flexural isostatic loading, compaction, slope failure and other processes, are represented by Tetzlaff and Harbaugh (1989), Griffiths and Paraschivoiu (1998), Griffiths et al (2001), Liang et al (2005), Li et al (2004Li et al ( , 2006Li et al ( , 2007Li et al ( , 2008 and Salles et al (2010). Sedsim is controlled by a number of input parameters, for example, relative sea level/base-level curve, initial topography/ bathymetry, tectonic movement, sediment input rates etc.…”
Section: The Sedsim Programmentioning
confidence: 99%
“…Since 1994 Sedsim has been widely applied in hydrocarbon exploration and prediction (e.g., Griffiths and Paraschivoiu, 1998;Griffiths et al, 2001), and numerous researchers have adopted Sedsim to simulate and evaluate a variety of depositional systems.…”
Section: The Sedsim Programmentioning
confidence: 99%
See 1 more Smart Citation
“…The results reflect possible changes in sediment distribution over time as a function of the changing depositional environment. Past studies have demonstrated the value of this approach Griffiths & Paraschivoiu 1998;Koltermann & Gorelick 1992;Martinez & Harbaugh 1993). Any computer modelling is only as good as the validity of the input data and the algorithms used in the program.…”
Section: Sedsim Stratigraphic Forward Modellingmentioning
confidence: 99%